2019
DOI: 10.1002/berj.3531
|View full text |Cite
|
Sign up to set email alerts
|

An ethical analysis of how ESL teachers construct their professional identities through the use of information technology in teaching

Abstract: While there is growing recognition of the mutually shaping relationship between teaching with information technology (IT) and teachers’ beliefs, skills and self‐efficacy, there has been a paucity of research attention on the construction of teacher identity during actual IT‐assisted in‐class teaching and out‐of‐class networking with students, in a full institutional and social context. This study investigates how a group of secondary school English as a second language (ESL) teachers regulated their teaching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Somekh 2007;Kali, McKenney, and Sagy 2015). Research also explored how technologies frame professional learning for students and educators (Murray and Kidd 2016) or the use of online tools for teaching and personal learning (Bergviken et al 2018;Gu and Lai 2019). But in a systematic review of research into online ITE (pre-pandemic), Dyment and Downing (2020, 329) conclude that 'the present research base is fragmented and consists of disparate and unrelated studies that rarely cross-reference each other'.…”
Section: The Practicum and 'Practical Learning' On And Offlinementioning
confidence: 99%
“…Somekh 2007;Kali, McKenney, and Sagy 2015). Research also explored how technologies frame professional learning for students and educators (Murray and Kidd 2016) or the use of online tools for teaching and personal learning (Bergviken et al 2018;Gu and Lai 2019). But in a systematic review of research into online ITE (pre-pandemic), Dyment and Downing (2020, 329) conclude that 'the present research base is fragmented and consists of disparate and unrelated studies that rarely cross-reference each other'.…”
Section: The Practicum and 'Practical Learning' On And Offlinementioning
confidence: 99%
“…However, only a few approaches have been assessed in order to determine the strengths and weaknesses of peer review of teaching (Biasutti, Baz, & Alshawa, 2016). Therefore, research efforts have been exerted to explore the interplay between different forms of power, practices of policy and teacher identity (as cited in Gu & Lai, 2019).…”
Section: Lecturersí Professional Development In Teaching Content Subjectsmentioning
confidence: 99%
“…They found that the students and teachers had different perceptions about the application of those ethical principles, including discipline according to law and school policy. Gu and Lai (2019) investigates secondary school English (ESL) teachers regulated their teaching and practices and constructed their identities in relation to governmental requirements for the use of IT in teaching. They found that there was an identity dilemma for teachers.…”
Section: Introductionmentioning
confidence: 99%